Change Management as a reflection on strategic initiatives in a learning organisation : dizertačná práca - Hennemann, Jan Nicolai (Žilinská univerzita v Žiline, Fakulta prevádzky a ekonomiky dopravy a spojov, 2024)
This dissertation addresses the escalating challenge faced by organizations during periods of polycrisisa simultaneous occurrence of multiple crises such as financial instability, health emergencies, and climate change, which have been notably pervasive over the last 15 years. These crises challenge traditional management paradigms, pushing organizations towards the brink of failure, thereby necessitating a reevaluation of leadership and management strategies.Jan Nicolai Hennemann's research aims to bridge the theoretical and practical gaps in effectively managing polycrises within organizational settings. By synthesizing lessons from conflict, crisis, and change management, the study provides a multidisciplinary approach to fostering resilience and adaptability in organizations. The dissertation proposes a transformative framework that incorporates an extensive review of literature, expert consultations, empirical data, and case studies to develop innovative management practices that are responsive to the complexities of a polycrisis environment.The dissertation unfolds over eight chapters, methodologically structured around three phases and seven milestones, to navigate the theoretical underpinnings and practical applications of managing in turbulent times. It critically evaluates current organizational strategies against the backdrop of global crises like the 2008 financial crisis, COVID-19, the ongoing security crisis and the escalating climate change crisis. Through a detailed analysis of these crises' origins, impacts, and the management responses, the research underscores the necessity for organizations to shift from traditional, linear problem-solving approaches towards more integrated, dynamic, and systemically-informed practices.Key findings emphasize the importance of adopting a 'transformative loop'a strategic iterative process that enables organizations to continuously learn and adapt in response to evolving global challenges. The dissertation concludes with practical recommendations for leaders to cultivate resilience through enhanced preparedness, agile response strategies, and inclusive stakeholder engagement, ensuring sustained organizational success in an era defined by frequent and complex disruptions.By bridging theoretical insights with practical strategies, this dissertation contributes significantly to the literature on leadership and organizational studies and offers a robust framework for practitioners aiming to navigate the intricacies of polycrisis management effectively.